Internalisasi Kabar Baik Dalam Nyanyian Jemaat - Kezia Tirta Rahardja; Maria Armalita Tumimbang (Psalmoz: A Journal of Creative and Study of Church Music, 2020)
In a song, the lyrics or poetry is very important, because through the lyrics, it can be seen the message contained in the song, so that it can affect the feelings of those who hear it. The purpose of this study is to analyze Congregational songs that have Good News elements and see how the process of Internalizing Good News in Congregational Songs especially in the GMIM Eben Haezer Suwaan Congregation. This study used a qualitative method conducted at GMIM Eben Haezer Suwaan in June - August 2017. The research data was collected through Observation, Interview, and Documentation as well as the results of data analysis and interpretation of data obtained that (1) Does the song in the Congregational song have elements Good news. (2) What is the process of Internalizing Good News in Congregational Singing at GMIM Eben Haezer Suwaan. The findings of this study are recommended for the Jama'at regarding the function of Congregational Singing which is used in Internalizing Good News, also for evangelizers in using Congregational singing as a means of assisting the Jama'at in internalizing the Good News.